2018
DOI: 10.1186/s12886-018-0797-z
|View full text |Cite
|
Sign up to set email alerts
|

A case of scleritis associated rheumatoid arthritis accompanying an intraocular elevated lesion

Abstract: BackgroundScleritis and/or uveitis sometimes accompanies patients who suffer from rheumatoid arthritis. However, few studies have reported scleritis and/or uveitis accompanying a fundus elevated lesion, such as an intraocular tumor. In this study, we report a case of rheumatoid uveitis associated with an intraocular elevated lesion.Case presentationA 66-year-old female visited another eye clinic and was diagnosed as bilateral anterior uveitis, and was prescribed steroid eye drops for treatment. She had previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Although neuropsychological damage is not usually associated with RA, recent studies have suggested the possibility of developing cognitive impairment, responsible for the alteration of daily life in patients with RA [ 58 ]. Cognitive function includes many neuropsychological domains, dealing with orientation, attention, concentration, judgment, problem-solving, memory, and visual-spatial conception [ 59 ].…”
Section: Extra-articular Manifestations In Rheumatoid Arthritismentioning
confidence: 99%
“…Although neuropsychological damage is not usually associated with RA, recent studies have suggested the possibility of developing cognitive impairment, responsible for the alteration of daily life in patients with RA [ 58 ]. Cognitive function includes many neuropsychological domains, dealing with orientation, attention, concentration, judgment, problem-solving, memory, and visual-spatial conception [ 59 ].…”
Section: Extra-articular Manifestations In Rheumatoid Arthritismentioning
confidence: 99%
“…In a previously done clinical survey, it has also been observed that these patients may present early but their diagnosis is often delayed up to seven months thus affecting the prognosis of the disease. 4 In our case, there was not a single day's delay from the beginning which is what made our patient regain his vision in just a few months' time.…”
Section: Discussionmentioning
confidence: 52%
“…6 Ocular pain is the most common symptom, reported in 64% of patients with posterior scleritis, alerting the physician regarding an inflammatory condition. 4 B-scan ultrasonography is an important tool in diagnosis that may show scleral nodular thickening and diffuse hyper echogenicity, unlike choroidal neoplasms where there can be moderate hyper echogenicity or a hypoechogenicity. 3,7 We report an atypical presentation of posterior scleritis and choroiditis in a young man who came with a two-week history of a sudden decrease in right eye vision, redness, and moderate ocular pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scleritis, for example, when associated with RA, can lead to severe ocular complications and is thought to be caused by the deposition of the immune complex found in the necrotizing collagen associated with the sclera [53]. Most cases of scleritis are treated with immunosuppressive drugs and have a good resolution, although some refractory cases are more aggressive and resistant to steroid therapies [54].…”
Section: Extra-articular Manifestations In Rheumatoid Arthritis: Neurological Involvementmentioning
confidence: 99%